2012
DOI: 10.1002/etc.1719
|View full text |Cite
|
Sign up to set email alerts
|

Using toxicity testing to evaluate electrochemical reactor operations

Abstract: In the present study, the Microtox® test was used to track the toxicity of electrochemical effluents to the marine bacteria Vibrio fischeri as a function of reaction time. When electrochemistry was used to degrade aqueous phenol using different reactor configurations, two reaction pathways were identified, chlorine substitution and oxidation, depending on whether the electrolyte contained chloride. For a boron-doped diamond (BDD) anode, electrochemistry using Na₂SO₄ electrolyte produced a significantly more to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
(40 reference statements)
4
9
0
Order By: Relevance
“…The reaction progressed much more slowly in the presence of NaNO 3 , which is not expected to participate in the reaction or produce reactive chlorine. Therefore, this electrochemical oxidation using a BDD anode, in the presence of the NaCl electrolyte, likely produces large concentrations of active chlorine, which may contribute to the degradation of contaminants, similar to reports with other electrodes (Murugananthan et al, 2011;Saylor et al, 2012). Although not directly measured in this study, the formation of organochlorinated intermediates, as well as chlorate, may present further concerns when using the NaCl electrolyte (Sirés et al, 2014).…”
Section: Minimizing Impacts Of Secondarysupporting
confidence: 77%
See 2 more Smart Citations
“…The reaction progressed much more slowly in the presence of NaNO 3 , which is not expected to participate in the reaction or produce reactive chlorine. Therefore, this electrochemical oxidation using a BDD anode, in the presence of the NaCl electrolyte, likely produces large concentrations of active chlorine, which may contribute to the degradation of contaminants, similar to reports with other electrodes (Murugananthan et al, 2011;Saylor et al, 2012). Although not directly measured in this study, the formation of organochlorinated intermediates, as well as chlorate, may present further concerns when using the NaCl electrolyte (Sirés et al, 2014).…”
Section: Minimizing Impacts Of Secondarysupporting
confidence: 77%
“…The effluent toxicity was a major concern to the WERF expert workgroup for ultimate disposal of contaminated waters treated in emergency response scenarios (Striano et al, 2011). Limited studies have reported that AOP treatments yield degradation intermediates that can be more toxic than the parent compound (Saylor et al, 2012;Haidar et al, 2013). A variety of microbial toxicity assays demonstrate potential eco-toxicity, as well as toxicity to activated sludge from WWTWs.…”
Section: Bdd+h 2 O Bdd ⋅ Oh + H + + E − (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The improper discharge of industrial effluents containing toxic organic and inorganic pollutants lead to severe water contamination and their coexistence in the aquatic systems is a threat to the regulating authorities all over the world . The current problem has exerted pressure on the scientific community to look for an economical and efficient method that could remove these pollutants from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,6-TCP and chromium are common environmental pollutants, and classified as priority pollutants by the U.S. Environmental Protection Agency (EPA) [5][6][7][8]. The mixture of chlorophenol and chromium can be easily found in many waste streams, for instance tannery effluents.…”
Section: Introductionmentioning
confidence: 99%